Over grenzen en generaties heen : Lessen voor de eenentwintigste eeuw (Lessen voor de eenentwintigste eeuw, 2014)
Scientific research has no final agreement or hypotheosis. It devotes itself constantly. At any time, enter new academics in the wake of their teachers, one makes use of new methods, and develop new interests. Evolves not only the nature of the scientists and their methods, even their research object changes. Especially in the field of politics and the world economy, we are in revolutionary times. The geopolitics of the U.S. and Europe compared to emerging countries such as China, India and Brazil change drastically and in the Arab countries, the desire grows to real democracy. Meanwhile, the pressure on the capacity of our blue planet further. In 2050, there may be 9 billion people. Will there be enough food? What energy will we use? What are our future needs in a sustainable way? In what kind of vehicles we will move us?